Semi analytical iterative method for solving Klein-Gordon equation / Mat Salim Selamat ... [et al.] - Selamat, Mat Salim; Muhidzir, Afifah; Abd Razak, Nor Nazierah; Hassanuddin, Zakila Amira (Universiti Teknologi MARA Cawangan Pahang, 2020)
In this article, a semi analytical iterative method had been applied to solve a type of partial differential equation namely Klein-Gordon equation. Four examples of linear and nonlinear Klein-Gordon equations were considered to show the performance of the method. The results obtained revealed the effectiveness of this method.